Oxidation Lipid on Fish Cake Catfish (Pangasius sp.) Dissolved in The Extract of Bay Leaf (Eugenia polyantha) - Mahiastuti Tribuana Tungga Dewi; Boedi Setya Rahardja; Agustono Agustono (Universitas Airlangga, 2019)
Catfish (Pangasius sp.) As a source of animal protein. Fish catfish have a thick white meat so that it can be processed into a wide range of diversified products. The process of fried fish cake can result in fat or autooxidation process. Autooxidation can be inhibited by the presence of antioxidant compounds. One source of natural antioxidants are bay leaf Eugenia polyantha.This research was carried out by experimental methods and the use of experimental design of randomized Complete Design (RAL). RAL is used when the material and condition of the experiment are homogeneous. This research consists of four concentrations of extract treatment bay leaf, namely 0%, 10%, 20%, 30%. Fish cake has been fried done soaking for 30 minutes. Water content showed no significant difference (p> 0.05) at 24 hours to 28, this indicated that the addition of bay leaf extract did not affect the moisture content during storage. The high water content at 0 hour is caused by the process of soaking the fish cake in the extract solution. The highest value is shown by the concentration of 30% at the hour to 0 that is 52.78%, this indicates that the fish cake by soaking can meet the quality score SNI 7757:2013 which is a maximum of 60%. The fat content in the fish cake continues to decrease, indicating the occurrence of oxidation during storage. Levels of TBA in fish cake continue to increase that can be slowed by the extract of bay leaves with a concentration of 30%.